Nocturnal enuresis: A topic review and institution experience - John Michael DiBianco (Thieme Medical and Scientific Publishers Pvt. Ltd., 2014)
The objective is to provide a review of nocturnal enuresis (NE), including its epidemiology, etiology, pathophysiology, evaluation, and current management. We also set to provide further insight on the treatment of this condition from the experience derived from patients cared for at our tertiary‑care institution. NE affects approximately 15% of all children at 5‑year‑old, affecting boys more frequently than girls. At our large university tertiary pediatric urology center, NE and incontinence, in general, is one the most common chief complaints prompting urologic care. In this review, we examine the condition in detail, highlighting specific goals of the initial evaluation and treatment. We contrast the commonly implemented treatment recommendations, available from the literature with strategies we have found valuable from our extensive experience in treating patients with this disorder. Using current urologic reference textbooks, book chapters, Medline, journal articles and reviews describing the many aspects of NE were reviewed in order to describe NE and the current practices at our institution. Although, this is not a systematic literature review, it includes relevant available research, institutional experience and urological expert opinion and current practices at a tertiary state health facility. The treatment of NE remains a challenge for many pediatricians and pediatric urologists. This likely stems from the multiple possible etiologies of the disorder. We have established a treatment algorithm at our institution, which we have found successful in the majority of our patients. This consists of starting patients on urotherapy, then offering both the enuresis alarm device and medication therapy as first line treatments, and finally adding anticholingerics for combination therapy. Our hope is with further research the treatment of NE will continue to improve.